Pengaruh Brand Ambassador, Brand Image, dan Kualitas Produk terhadap Keputusan Pembelian Produk Moisturizer Glad2Glow - Intan Nur Alifah; Tri Ratna Pamikatsih (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Amid intensifying competition in the beauty sector, this study investigates how brand ambassador, brand image, and product quality relate to purchasing decisions for Glad2Glow moisturizer products. The research adopts a quantitative design implemented through a survey, where primary data were obtained via questionnaires administered to 100 respondents with prior experience using the product. Data processing was conducted using multiple linear regression with SPSS. The empirical results indicate that, on a partial basis, brand ambassador and brand image do not exert a significant influence on purchasing decisions, implying that consumers do not primarily rely on brand representation or perceived image when making purchase choices. Conversely, product quality demonstrates a positive and significant effect, reflecting that functional value and performance play a central role in meeting consumers’ skincare expectations. When considered simultaneously, the three variables account for 59.9% of the variation in purchasing decisions. These findings underscore the strategic importance of consistently maintaining product quality to enhance competitive positioning in the market. Furthermore, the study suggests that while marketing elements such as brand ambassador and brand image remain relevant, greater emphasis should be placed on product-oriented improvements to better align with consumer priorities.